Promoting the menstrual health of adolescent girls in China. (20th June 2016) - Su, Jing Jing; Lindell, Deborah
Abstract: In China, nurses have limited presence in schools, thus, adolescent girls often lack accurate information about menstrual health, which may lead to incorrect and unhealthy menstrual‐related behavior. This study investigated the effects of a culturally and developmentally tailored nursing intervention on the menstrual health of adolescent girls in China. Following institutional review board approval, adolescent girls aged 12–15 were recruited from two schools. A quasi‐experimental, pretest‐posttest design examined the effects of five interactive education sessions on menstrual health. The final sample included 116 adolescent girls. Significant improvement was observed in the intervention group regarding menstrual knowledge, confidence in performing menstrual healthcare behavior, and dysmenorrhea related self‐care behavior. A nurse‐managed education program improved adolescent girls' menstrual knowledge, promoted a more positive attitude, encouraged confidence, and improved pain relief practice. We recommend that professional nurses globally advocate for school nursing and routine menstrual health education for adolescent girls.